L.A.M.P. - Tasrip, Nor Asmara; Khairil Mokhtar, Nur Fadhilah; Hanapi, Ummi Kalthum; Ali, Md. Eaqub; Cheah, Yoke Kqueen; Mustafa, Shuhaimi; Mohd Desa, Mohd Nasir (Universiti Putra Malaysia Press, 2017)
Despite legal regulations, undesired porcine DNA has been found in food products labelled as halal, reflecting potential fraud or contamination. For example, porcine DNA traces have been detected in lacto-ovo-vegetarian candies, corroborating unethical or unsafe practice during the manufacturing stages. Therefore, disclosing full information on the ingredients contained in commercial food products with proper authentication check is essential for consumers to know what they are actually eating, for religious and health concerns.